Improvement of implementation modernization 2G project using project management concept case study PT HTI west java region - Simarmata, Jefferson; Bekti, Rudy (The Indonesian Journal of Business Administration, 2016)
Abstract. XYZ is a global leader of ICT (Information and Communication Technology) solutions. Continuously innovating based on customer needs, XYZ are committed to enhancing customer experiences and creating maximum value for telecom carriers, enterprises, and consumers. In the field of professional services, XYZ has always demonstrated a willingness to establish a strategic partnership with the operators. This collaboration ensures improved network and service quality which enhances customer experience. This also positions XYZ to promote operational transformation concept while accelerating the adoption of the next generation network and service evolution. The whole industry will continue to see profound changes. These changes will be driven by the introduction of new technologies and dramatic changes in network architectures. XYZ closely collaborate with telecom operators and their industry customers to provide competitive and valuable service solutions. R operator appear to be the biggest operator in the country, which XYZ part of wireless market share. R operator is committed to providing the best service to its customers, one of the efforts is network modernization by swap BTS (Base Transceiver Station) existing with new BTS equipment for 2G to anticipate the high voice traffic and also reduce the operational cost of R operator. R operator signed a contract with XYZ Company for network modernization its entire telecom network 2G in West Java area. All 2G BTS will be swapped with new equipment with modern, efficient and future ready hardware. This thesis describe more specific on 2G network modernization project for R operator in West Java area which 596 system BTS existing vendor N change with XYZ BTS. Â In the project implementation there are some issues raised which effect the project such as delay completion time of project, number of sub-contractor transmission team inadequate, lack of monitoring and control project progress and there no pre-evaluate and categorize the risk in the project. Project Time Management and Project Risk Management the part of Project Management knowledge areas, Critical Path Method (CPM) and PERT analysis are used to analyze the business issue and to find the root cause of inefficient completion time of project. The root cause are: lack of Project Time Management knowledge, lack of Project Risk Management, lack of experience, limited sub-contractor resource, irregular status review meeting and lack of risk management knowledge. Based on Project Management concept there are some business solution alternative to improve implementation modernization project become more efficient, which are: training scheduling technic, reduce completion time by increase number of sub-contractor team based on CPM analysis, create regular status review meeting and define and manage the project risk. The result of this research can used for the next modernization project or another project in XYZ.Â Keywords: Project Management, Project Time Management, Project Risk Management, completion time, scheduling technic, critical path, CPM, PERT.